Pendampingan Penulisan PTK Menggunakan Aplikasi Mendeley pada Guru SMP dan SMA Al-Qur’an An-Nawawiy Sooko Mojokerto - Oktaviani Permatasari; Khasbulloh Huda; Mohamad Johan Efendi; Rahmad Sholeh; Irwan Swandana; Ahfi Nova Ashriana; Didit Panji Saputra (Fakultas Teknik Universitas Cenderawasih, 2023)
The teacher's job is to educate and teach students. Teaching and learning activities are certainly not easy. Unachieved learning is caused by many factors including less than optimal teacher delivery, unacceptable learning methods, less fun learning models, so students become bored and learning motivation decreases. Of course there is a special way for teachers to deal with this problem which is better known as Classroom Action Research (CAR), but the teacher's lack of knowledge in writing and compiling this PTK so that teachers rarely use PTK on the grounds that it is difficult and cannot do it. For this reason, the purpose of this community service is to assist teachers in writing PTK using the Mendeley application, which teachers generally do not know, for Middle and High School Al-Qur'an an-Nawawiy Sooko Mojokerto teachers. The method used in this activity is in the form of training through lectures, question and answer and discussion as well as direct practice. The expected result of this service is that teachers for each subject can submit PTK articles in National Journals with ISSNs, with a maximum target time of 1 (one) month from carrying out the service and mentoring.